2022
DOI: 10.3233/bmr-210029
|View full text |Cite
|
Sign up to set email alerts
|

Differences between chronic low back pain patients in Germany and Thailand in terms of nature of disease and socioeconomic and psychological factors

Abstract: BACKGROUND: Worldwide, chronic low back pain (CLBP) is one of the most common causes of physical and psychological disabilities. The factors that affect low back pain (LBP) between Western and Eastern countries are different. OBJECTIVE: We assessed the factors associated with LBP and their impact in German and Thai CLBP participants. METHODS: This cross-sectional study was conducted in 100 Thai and 100 German CLBP participants. Data were collected before the participants received treatment in the outpatient re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…This study found that the type of country was a moderating variable in the relationship between psychological inflexibility and pain intensity or depression, significantly higher in chronic pain patients in western countries than in eastern countries. It is consistent with previous cross-sectional studies, which suggest that patients in Eastern countries may have a greater tolerance for pain (Thong et al, 2017 ; Yotnuengnit et al, 2022 ). This may be related to underlying cultural differences: stoicism is seen as a positive quality in Eastern cultures, whereas the inability to tolerate pain is seen as a sign of weakness (Narayan, 2010 ; Thong et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…This study found that the type of country was a moderating variable in the relationship between psychological inflexibility and pain intensity or depression, significantly higher in chronic pain patients in western countries than in eastern countries. It is consistent with previous cross-sectional studies, which suggest that patients in Eastern countries may have a greater tolerance for pain (Thong et al, 2017 ; Yotnuengnit et al, 2022 ). This may be related to underlying cultural differences: stoicism is seen as a positive quality in Eastern cultures, whereas the inability to tolerate pain is seen as a sign of weakness (Narayan, 2010 ; Thong et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%